A bivalent outer membrane vesicle-based intranasal vaccine to prevent infection of periodontopathic bacteria - Nakao, Ryoma; Hirayama, Satoru; Yamaguchi, Takehiro; Senpuku, Hidenobu; Hasegawa, Hideki; Suzuki, Tadaki; Akeda, Yukihiro; Ohnishi, Makoto (Vaccine, 2023)
Periodontal disease has become a serious public health problem, not only causing tooth loss, but also inducing chronic disorders of extra-oral organs. The present study assessed an intranasal vaccine strategy to prevent periodontal disease using outer membrane vesicles (OMVs) of two major periodontopathic bacteria, Porphyromonas gingivalis (Pg) and Aggregatibacter actinomycetemcomitans (Aa). We compared the morphology, composition, and immune activity between OMVs of Pg strain ATCC 33277 and Aa strain Y4. Aa OMVs had a smoother surface and stronger lipid A activity compared to Pg OMVs. The in vitro immune activity elicited by Aa OMVs in macrophage-like cells was remarkably stronger than that of Pg OMVs. Intranasal immunization of mice with Aa OMVs alone resulted in robust, humoral immune responses in blood and saliva. Despites the intrinsically low mucosal immunogenicity of Pg OMVs alone, using Aa OMVs as a mucosal adjuvant strongly enhanced Pg-specific immune responses, resulting in both serum IgG and salivary IgA, both of which aggregated Pg and Aa cells. Furthermore, Aa OMVs were found to be a more potent mucosal adjuvant than Poly(I:C) in the context of enhancing the production of Pg-specific IgG (especially IgG2a) and IgA. In addition, in a randomized, blinded study, mice oral challenged with Pg and Aa after intranasal immunization with Pg OMVs and Aa OMVs had significantly decreased numbers of both microorganisms compared to mock-immunized mice. Furthermore, in an intracerebral injection mouse model, there were no serious adverse effects on the brain even after administrating a dose of OMVs as same as that used for intranasal administration. Taken together, the bivalent OMV intranasal vaccine may be effective in preventing colonization of periodontopathic bacteria in the oral cavity and related systemic disorders associated with periodontal diseases.